ALIH KELOLA PENYULUH KB DALAM KERANGKA INSTITUSIONAL: DESKRIPSI SITUASI PERMASALAHAN IMPLEMENTASI UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH DI BKKBN - Vita Listiani (Jurnal Manajemen Kepegawaian, 2019)
ABSTRACT This research aims to determine the form of institutional framework of state policy and collective action of work units in the implementing agencies. It was an effort to examined government organizations in an institutional framework using Soft Systems Methodology (SSM) with research interest orientation. The data was collected at the National Population and Family Planning Board (BKKBN), which is an institution that has been authorized to manage Family Planning (FP) field workers as a consequence of the enactment of a legislation about Regional Government. The number of FP field workers who employment status were being transferred from district / city government civil servants to BKKBN civil servants have reached approximately 15,000. They were spread throughout Indonesia with varying geographical characteristics and HR capacity. Their lowest management unit was at the provincial level. This condition drove BKKBN to formulate a policy infrastructure that could be a guidance in the implementation of the governance of FP field workers. Empirically, this study was examined through the perspective of New Institutionalism which focuses more on organizational level. Keywords: Management of FP field workers, BKKBN, New Institusionalism, Soft Systems Methodology